Odškodninska odgovornost sodnika in odgovornost države zanj - Zobec, Jan (Pravni letopis, 2013)
Since judges are only humans, it holds for them as well: to err is human (thus judicial). Andwhere the error is, there (mostly) is harm. However, the question arises, whether there is also a liability - and if it is, who should be held liable. The author seeks the answer to the question, which errors entail tort liability, which subject is held liable and on which ground. He argues that the damage committed by judicial misconduct constitutes a public-law relationship between the state (which has caused the damage by its authoritative act) and the civil subject as the impaired person. According to the general (and self-evident) prohibition on the unlawful exercise of the state's power, the author argues for the ex-personification of the state's tortliability. As fault has always been ascribed to an individual and particular tortfeasor, it should,in the cases of judicial misconduct, be absorbed by the unlawfulness of the state body's act. What essential here is the mere fact that the damage has been caused by an unlawful act of the judicial power. Since judicial misconduct is at stake, the focus should be paid on the proper exercise of the state's power rather than on the particular individual who has beenexercising this power. The attention is thus focused not on particular judge and his conductb ut on the question how the state authority should (in that particular case) act and exercise its jurisdiction. The author discusses the question of causation (foremost from the view of two cases of the Supreme Court of Slovenia) and the significance of the jurisprudence of the CJEU. He points out that the CJEU's main goal is the assurance and the establishment of the uniform application of the EU law, rather than safeguarding of the individuals' rights.
Keywords: država; napake; odškodninska odgovornost; pravna zmota; pravosodje; sodniki; state